Descriptive Analysis on Writing Exercises in The English Textbook on Students’ At The Tenth Grade of SMA Negeri 1 Gido in 2022/2023 - Selfin Indah Sari Zendrato; Hasrat sozanolo Harefa; Afore Tahir Harefa; Yasminar Amaerita Telaumbanua (Journal on Education, 2023)
Writing exercises can be used to introduce students to a literary text, to motivate and help them to create their understanding of the text, and articulate their own interpretation of the text. Writing exercise is primarily on grammar, students will get good marks if the texts are free from errors or have only just very few errors. Therefore, the objectives of this research were to know the types of writing exercises in the English textbook and to know the compatibility based on the syllabus. The method used in this research was descriptive qualitative. This research is about content analysis design. The data was collected by using documentation. The steps to analyze the exercises are reading the exercises suggested by the syllabus, identifying the number of writing exercises in English textbook and classifying based on the competency and skill which emphasizes in the exercise.After observing the English textbook, then matching it with the 2013 curriculum, the researcher found several types of writing exercises and counted the compatibility with the syllabus. First, the researcher found 4 types of writing exercises in the English textbook, which is (a) Completing texts/sentences, (b) Writing sentence dealing with grammar, (c) Writing short functional text, and (d) Developing vocabulary into sentences. Second, the compatibility of writing exercises in English textbook with the syllabus, the result show that the percentages offer to the schema of quality classification by Arikunto is 71%. It means the score is good, and the textbook can be used as a media in the learning process. From this result, it can be concluded that this textbook compatible with the 2013 curriculum and can be recommended as teaching-learning media in the class.